2016
DOI: 10.18203/2349-3291.ijcp20160144
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical profile and certain modifiable risk factors associated with acute respiratory infection cases admitted in a tertiary care hospital

Abstract: Acute respiratory infection (ARI) is an acute infection of any part of the respiratory tract and related structures including paranasal sinuses, middle ear and pleural cavity. It included all infections less than 30 days duration except those of the middle ear where the duration of an acute episode is less than 14 days. 1 Globally on an average, children below five years of age suffer five episodes of ARI per child per year, thus accounting for about 238 million attacks. Consequently, ARIs are responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Acute malnutrition was significantly associated with childhood ARI in this study. Studies from India have previously highlighted nutritional status as being a significant risk factor for childhood ARI, with 2.4-to 7.1-fold increased odds of ARI in those who are malnourished (Goel et al, 2012;Mir et al, 2012;Arun et al, 2014;Naik et al, 2016). This may be because malnutrition predisposes to an immunodeficient state, which increases the risk of respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…Acute malnutrition was significantly associated with childhood ARI in this study. Studies from India have previously highlighted nutritional status as being a significant risk factor for childhood ARI, with 2.4-to 7.1-fold increased odds of ARI in those who are malnourished (Goel et al, 2012;Mir et al, 2012;Arun et al, 2014;Naik et al, 2016). This may be because malnutrition predisposes to an immunodeficient state, which increases the risk of respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…15 Passive smoking observed in present study was not statistically significant, but study done by Naik et al, found that deaths were more in cases with a family history of smoking. 16 Children with duration of symptoms <4 days before hospitalization stayed for <7 days in the hospital, irrespective of age group in the present study. Similar result was observed in a study by Naik et al 16 Among the 92 children presented with acute respiratory infection fever was present in 97 % of children, cough was present in all the children studied.…”
Section: Discussionmentioning
confidence: 56%
“…16 Children with duration of symptoms <4 days before hospitalization stayed for <7 days in the hospital, irrespective of age group in the present study. Similar result was observed in a study by Naik et al 16 Among the 92 children presented with acute respiratory infection fever was present in 97 % of children, cough was present in all the children studied. Central cyanosis was seen in one child, a 5-month-old baby presented with very severe pneumonia requiring ventilation.…”
Section: Discussionmentioning
confidence: 56%